PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP HASIL BELAJAR IPA SISWA KELAS IV - Aisyah, Putri; Safrihady, Safrihady; Kamaruddin, Kamaruddin (STKIP Melawi, 2025)
Abstract: The purpose of this study was to state whether or not there was a difference in science learning outcomes of students using the Children Learning In Scince (CLIS) Learning Model with students who used the direct learning model for grade IV. The subjects in this study consisted of two classes, namely class IV A with 20 students and class IVB with 20 students. There were three instruments used in this study, namely test sheets, observation sheets, and documentation. This type of research is Quasi Experimental, where class IV B as an experiment that will be given treatment and class IV A as a control class that is not given treatment. The data analysis technique used a two-sample t-test, effect size, and percentage. Research results; 1) There is a difference in the science learning outcomes of students who use the Children Learning In Science (CLIS) Learning Model with students who are taught with a direct learning model, the calculation results show t_count = 5.559 and t_table = 1.686; 2) The Children Learning In Science (CLIS) Learning Model has a large influence on the science learning outcomes of grade IV students of SDN 85 Singkawang, with the calculation results of the effect size of 1.49; 3) The implementation of the Children Learning In Science (CLIS) Learning Model is in the very good category for science learning outcomes, with the calculation results of 92.66%. So from the results of the research that has been done, it can be concluded that